The procedural aspects of South Africa's Anti-dumping legislation and its compatibility with the World Trade Organisation Anti-dumping Agreement - Oluyeju, Femi (University of Pretoria, 2021)
Mini Dissertation (LLM (International Trade and Investment Law in Africa))--University of Pretoria, 2021.